(untitled) (Research, Society and Development, 2021)
Head and neck cancers (HNC) have a high morbidity and mortality rate, even after technological advances in conventional cancer therapy. Thus, the study of adjuvant therapies, such as the use of polyphenols, presents potential results in the treatment of HNC. This review aimed to identify the effects of using polyphenols in the treatment of HNC. An integrative review was carried out using the PICo tool, performing the search in four electronic databases, using the terms “Polyphenols”, “Head and Neck Cancer” and “Therapy”, in addition to their correspondence in English and Spanish. A total of 25 articles comprised the study sample. The data extraction strategy sought to identify mainly the compound, mechanism of action, main outcomes, level of evidence and study design. The most prevalent study design was “review” and “in vitro” and the review identified that the most used compounds were Curcumin and Resveratrol. Almost unanimously, the studies pointed to antineoplastic effects of polyphenols in HNC, activating mechanisms of cell death and tumor reduction, through several ways. Thus, considering the effect of conventional therapies for HNC, as well as its clinical outcome, the use of polyphenols is a potential and promising option, instigating the development of research that addresses in detail the cellular mechanisms, adverse effects and dosages.